Invest wisely in young people - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Responding to the letter from I Thuwein of Tanzania in Spore 86 about poverty reduction, Wale Adeyinka, of the Federal College of Forestry in Ibadan, Nigeria, refers to his new government s poverty alleviation programme and suggests a link between...